Analysis of the impurity flow velocity in a wide plasma parameter range for deuterium and hydrogen plasmas in the divertor legs of the stochastic layer in LHD. (December 2018) - Kuzmin, A.; Kobayashi, M.; Nakano, T.; Kawamura, G.; Hasuo, M.; Fujii, K.; Morisaki, T.; ,
Highlights: Carbon velocities are measured for a wide plasma parameter range in LHD divertor. In all cases carbon flow velocities are 5–35 km/s. Different charge states of carbon impurity have different velocities. Velocities in hydrogen plasma are faster than in deuterium by a factor of 1.4–2.0. Simulations with EMC3-EIRENE code show same qualitative trends as experiments. Abstract: Impurity flow velocity measurements have been conducted for different magnetic field configurations in a wide plasma parameter range in the divertor leg region of LHD for understanding of the edge impurity transport. In all cases (densities, magnetic configurations, hydrogen (H) & deuterium (D) discharges), flows of several tens of km/s are observed. It is found that the flow in thick stochastic layer is faster than in thin stochastic layer configuration by a factor of 3. Different velocities of different charge states of carbon impurity are observed. The simulation with EMC3-EIRENE code shows similar trend as the experiments, but only qualitatively: faster flow in H compared to D discharges due to the mass effect, faster flow in the case of thick stochastic layer. However, synthetic spectra show discrepancy with experiments in the absolute Doppler shift, where the impurity velocity in the experiments is one order faster compared to the simulations.